Efektivitas Mendeley sebagai Software Bantu untuk Manajemen Referensi - Nurwahyu Nurwahyu; Syifaun Nafisah (Pustabiblia: Journal of Library and Information Science, 2021)
The purpose of this research is to be able to determine the effectiveness of Mendeley software that can be used as an aid software for reference management. The research method used is quantitative descriptive. The unit of analysis in this study is Mendeley. Data collection techniques used are exploration (browsing), searching (searching) on the software website under study and making a checklist of characteristics of software quality based on its function as a reference management software and with relevant library studies. The results showed that Mendeley’s software was stated to be very effective because of the 8 (eight) feature indicators stated 98.75% of the checklist indicators were available. Thus the quality of Mendeley’s software is very effective to be implemented, so that this software can be used to facilitate or integrate with other software in writing scientific papers in search of the scientific references they need.